(untitled) (Libellarium: journal for research in the field of information and related sciences, 2011)
E-marketing started to develop as a result of an extensive advancement of information and communication technology, i.e., changes prompted by that process in the field of electronic media in particular over the last decade. As a contemporary concept, e-marketing offered answers to questions organisations were dealing with in seeking to bring their products and services closer to as many customers as possible in the new circumstances. Taking the importance that e-marketing already has as a starting point, the authors conducted an investigation with an aim to establish to what extent Croatian publishers use e-marketing in their operations and how they manage its implementation. As part of the research, the perception that marketing staff employed by Croatian publishing companies have of e-marketing was also investigated. In spite of its importance, this issue has not been adequately studied until now, which was an additional motive to carry out the research. The research was conducted among a sample of 61 publishing companies in the Republic of Croatia. It was precisely the unwillingness of some publishers to cooperate combined with insufficient number of scientific papers in the field of use of e-marketing in the publishing trade that can be underlined as the most significant problem in this research. In addition to descriptive statistics, Mann-Whitney and Kruskal-Wallis tests were used to analyse the data. The results have shown that last year almost one third of interviewed companies did not earmark funds for e-marketing. On the other hand, there were few publishers who spent more than half of the total funds, allocated for marketing activities, for that purpose. Along those lines is also the fact that respondents are not particularly satisfied with effects of e-marketing. Significantly more favourable results were obtained when it comes to publishing company web sites, i.e., the use of such a form of promotion. Namely, a large proportion of Croatian publishers have a web site. Respondents stated that their sites were mostly registered with the search engines and that they were regularly updated. There are also a significant number of companies offering on-line purchase of products. Although the proportion of companies using at least some form of e-marketing is rather large, simpler methods of advertising and establishing contact with customers are in the majority. On average, interviewed marketing staff evaluated their knowledge of e-marketing as good. Based on the obtained results, the authors have concluded that, with the exception of individual cases, Croatian publishers have not yet fully recognised the importance and possibilities of e-marketing. Arguing that there are numerous obstacles to its full implementation in the publishing business, respondents do not agree that thorough changes are needed in the way they conduct marketing activities, although they are increasingly using e-marketing in their operations. It is likely that this attitude is largely the result of their belief that Croatian population is insufficiently skilled in using information and communication technology and an opinion that e-marketing is not more efficient than traditional marketing. The authors have concluded that, in terms of characteristics used for their categorisation, marketing staff have a rather uniform attitude towards e-marketing. Research study whose results have been presented in this paper contributes to a better understanding of various aspects of the use of e-marketing in the publishing trade. As such, it can be used to improve e-marketing management, thereby improving overall performance, which represents its most important merit.